How Protestant Missions Transformed the Indo-Myanmar Frontier - Chophy, G. Kanato (Religion compass, 2025)
What makes the Indo-Myanmar frontier is the 1,021-mile borderline between India and Myanmar. Notably, this frontier region lies at the junction of East, South, and South East Asia, forming a kind of geopolitical space where the culture, economy, and politics of India, Myanmar, China, and Bangladesh have exerted considerable influence. Though hemmed in by these nations, the Indo-Myanmar frontier region stands out for its Western Protestantism roots, which has far-reaching impact on the society, politics, and culture of the region’s diverse ethnic communities. This article explores how the Protestant missions, especially the American Baptist mission, starting from the second half of the nineteenth century transformed this backwater of British India into arguably one of the most successful Christian missionary legacies in the whole of Asia.